Hubungan Strategi Pemberdayaan Dengan Empowerment Pada Penderita Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Sibela Kota Surakarta - Arifin, Annisa Zulfa, Okti Sri Purwanti, S.Kep., M.Kep., Ns., Sp.Kep.M.B (2017)
THE RELATIONSHIP BETWEEN EMPOWERMENT STRATEGY AND EMPOWERMENT IN CLIENT WITH DIABETES MELLITUS TYPE 2 IN THE AREA OF PUBLIC HEALTH SIBELA SURAKARTA Oleh : Annisa Zulfa Arifin ABSTRACT Diabetes mellitus is the cronic disease which is need extra treatment in order to increase the better life quality. One of the way to increase quality of life is doing empowerment strategy. The empowerment strategy need to increase DM patient so that it can increase the health of DM patient. The research aim to know the relation between strategy empowerment with empowerment in the DM patient type 2 in public health Sibela in Surakarta. This research is correlative research with cross sectional. The population of this research is all of the DM patient type 2 in public health Sibela in Surakarta about 218 patient. The sample of this research consist of 141 respondent got from proporsional stratified random sampling techniques. The collect of this data using questioner, besides the data analysis using correlation rank spearman. The result of rank spearment correlation gets from rs result 0,370 (p-value = 0,001), so the result is H0 not accepted. The conclusion of this research is empowerment strategy DM patient in range is enough, empowerment of DM patient type 2 mainly is medium, and there is a relation between empowerment strategy and empowerment in DM patient type 2 in working area regional occupational health center Sibela in Surakarta. Researcher suggest to the patient of DM to active for knowing about DM and ready to increase their treatment of DM. Keywords: the empowerment strategy, empowerment, type 2 DM patients